The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1111/j.1471-0528.2004.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tibolone in postmenopausal women receiving tamoxifen after surgery for breast cancer: a randomised, double‐blind, placebo‐controlled trial

Abstract: Objective To assess the effects of tibolone on climacteric symptoms, endometrium and serum lipid/ lipoproteins in postmenopausal women receiving tamoxifen after surgery for breast cancer. Design Double-blind, randomised, placebo-controlled, multicentre pilot study.Setting Hospital outpatient clinic.Sample Seventy postmenopausal women receiving tamoxifen following surgery for early breast cancer.Methods Women received 20 mg/day oral tamoxifen plus either 2.5 mg/day oral tibolone or placebo for 12 months. Main o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…In addition, Kroiss et al (24) have shown the efficacy of tibolone in the reduction of hot flushes in Table 3 The favorable therapeutic profile has led to the design of the ''Livial Intervention following Breast Cancer; Efficacy, Recurrence, and Tolerability Endpoints'' (LIBERATE) study, an international multicenter trial that has recruited >3,000 patients and that is expected to report a first analysis by end of 2007. The aim of the study is to show noninferiority of tibolone compared with placebo in respect to breast cancer recurrence and to show that tibolone is safe and effective in women with breast cancer and vasomotor symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Kroiss et al (24) have shown the efficacy of tibolone in the reduction of hot flushes in Table 3 The favorable therapeutic profile has led to the design of the ''Livial Intervention following Breast Cancer; Efficacy, Recurrence, and Tolerability Endpoints'' (LIBERATE) study, an international multicenter trial that has recruited >3,000 patients and that is expected to report a first analysis by end of 2007. The aim of the study is to show noninferiority of tibolone compared with placebo in respect to breast cancer recurrence and to show that tibolone is safe and effective in women with breast cancer and vasomotor symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Bjarnason et al [33] Gallagher et al [34] Kalogeropou-los et al [35] Kroiss et al [36] Lloyd et al [37] Year …”
Section: Studymentioning
confidence: 97%
“…5 Tibolone is a synthetic steroid with a clinical profile that differs from that of both classical estrogen-based HT, as well as from that of selective estrogen receptor modulators (SERMs). 13,14 Tibolone has shown its efficacy in reducing climacteric symptoms both in healthy menopausal women, 15 as well as in women receiving tamoxifen 16 or GnRH analogs 17 after surgery for breast cancer. The mode of action of tibolone differs from that of conventional estrogen receptor ligands.…”
Section: Introductionmentioning
confidence: 99%
“…There were no recurrences in either group during the 12-month study. 16 Although these findings are promising, definitive safety data can only come from a large, long-term controlled clinical trial such as the LIBERATE (livial intervention following breast cancer: efficacy, recurrence and tolerability endpoints) study. As tibolone has been increasingly prescribed preferentially in disease-free breast cancer patients who persistently seek help for their often disabling menopausal complaints, 25 such a trial is highly warranted.…”
Section: Introductionmentioning
confidence: 99%